ETIKA BELAJAR, BERDISKUSI DAN KETIKA DALAM SEBUAH FORUM MENURUT KITAB WASHOYA AL-ABAA LI AL-ABNAA - Mar'atus Sholikhah; Abdul Muhid (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
Man is a social being who needs each other to another creature. Therefore, it is supposed for every human being to keep each other's words and deeds in order not to cause bad things that are unwanted. Then we should always remember to always be ethical in all things, not be able to act. During this time, many people began to underestimate ethical problems. They act according to their own desires regardless of their creed. Ethics is the most important thing for human possession. Especially for students who are taking their time studying. Ethics is something that should really be considered either when studying inside or outside of class, while in discussion and when attending a forum. One of the keys to gaining success and useful science is good ethics. The purpose of this research is to revive especially for learners about the importance of ethics. The method used in this study is the Literature Review. This research is expected to develop and improve student ethics in order to obtain useful knowledge and success.